Epoxy functionalized polymer grafted magnetic nanoparticles by facile surface initiated polymerization for immobilization studies of Candida Antarctica lipase B - Afzal, Haq Asif; Ghorpade, Ravindra V.; Thorve, Asmita K.; Nagaraja, Sreeharsha; Al-Dhubiab, Bandar E.; Meravanige, Girish; Rasool, Sahibzada Tasleem; Roopashree, Teeka S. (Reactive & Functional Polymers, 2020)
Immobilization of Candida Antarctica lipase B (Cal-B) was done on the epoxy functionalized polymer (EFP) grafted magnetic nanoparticles (MNPs) via covalent attachment with the active epoxy groups. The EFP brushes were grafted on iron-oxide based MNPs by a facile surface-initiated atom transfer radical polymerization (ATRP) using activators generated by electron transfer (AGET) of glycidyl methacrylate (GMA). Each step of the surface modification, polymer grafting, and enzyme immobilization process on the polymer grafted MNPs was studied using Fourier transform infrared spectroscopy (FTIR). A thermogravimetric analysis (TGA) calculated the amount of engineered organic components, a transmission electron microscopy (TEM) visualized the core-shell formation of the MNPs, and a vibrating sample magnetometer (VSM) validated their magnetic properties at various modification stages. The lipase immobilization efficiency was described as a function of immobilization time, as well as, enzyme amount. The activity was characterized within a range of pH, temperature, kinetic parameters, resusability and storage stability, for both the free and immoblized Cal-B enzyme. The results of this study suggested that poly(GMA) grafted MNPs can be successfully used for the immobilization of Cal-B with improved efficiencies compared to those obtained with free soluble lipase. The reported enzyme immobilization method appears to be reproducible and scalable for industrial production.
Keywords: Cal-B enzymes; enzymes; Immoblization; Magnetic nanoparticles